Penggunaan Soilless Culture System Berisi Kompos Padat Bromelain Terinduksi Trichoderma sp. Terhadap Tanaman Selada (Lactuca sativa L.) - Nur Qolbi, Hana; Irawan, Bambang; Mahfut; Agustrina, Rochmah (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2024)
Lettuce plants are widely cultivated in Indonesia. Based on the 2019 Central Bureau of Statistics, the amount of lettuce plant production has decreased production, because the soil in Indonesia has decreased fertility and drought. To overcome this problem by switching the use of planting media in the form of Soilless Culture System (SCS) media containing compost on Trichoderma sp. induced bromelain. SCS media containing Trichoderma sp induced bromelain solid compost will produce media that will be rich in macro and micro nutrients so as to produce quality lettuce plants. The purpose of this study was to determine the effect of using SCS media containing compost on bromelain induced Trichoderma sp. and get the best dose of SCS media containing compost on bromelain induced Trichoderma sp. on lettuce plants. This study used a completely randomized design (CRD) with media treatments used, namely husks, vermicompost, compost, coconut husk, and bromelain solid compost with the ratio of P1 (2:1:1:2:2), P2 (2:1:1:2:3), P3 (2:1:1:2:4). The parameters observed were leaf area and levels of chlorophyll a, chlorophyll b, and total. The results obtained after being tested with ANOVA 5% and BNT 5% further test stated that the leaf area and chlorophyll a, chlorophyll b, and total levels had a significant effect and the best dose was obtained, namely treatment P3 (2:1:1:2:4).